2014
DOI: 10.1108/dpm-07-2013-0112
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to flood-induced public health risks in Sudan

Abstract: Purpose -The purpose of this paper is to analyze flood vulnerability vis-à-vis flood-induced health risks, and understand the relationship between them to suggest measures to reduce health risks in Sudan. Design/methodology/approach -This study compares the vulnerability to flood and health consequences in two communities in Aroma. This study compares the vulnerability of Aroma semi-urban vicinity and Tendellei rural village, in Sudan, to flood and health consequences. A set of socioeconomic and health indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Damages to the basic village health centers and education facilities also increase the susceptibility of rural households in Bangladesh [119]. Distance to emergency facilities, health centers, and metaled roads are important physical features that influence the susceptibility to flood in Sudan [126], Pakistan [127], and India [120]. Hence, availability and quality of infrastructure modify both flows and vulnerability.…”
Section: Infrastructuralmentioning
confidence: 99%
“…Damages to the basic village health centers and education facilities also increase the susceptibility of rural households in Bangladesh [119]. Distance to emergency facilities, health centers, and metaled roads are important physical features that influence the susceptibility to flood in Sudan [126], Pakistan [127], and India [120]. Hence, availability and quality of infrastructure modify both flows and vulnerability.…”
Section: Infrastructuralmentioning
confidence: 99%
“…Males are more susceptible to drowning (the largest cause of mortality from cyclones), and males are most susceptible to dying from cyclones (Doocy, Dick, Daniels, & Kirsch, 2013). Other factors that were associated with susceptibility include being female, being very young or elderly, living with a disability, being an ethnic minorities, lacking fluency in the country's primary language, having a female head of household, and having lower educational attainment (Abbas & Routray, 2014;Alderman et al, 2012;Bloetscher et al, 2016;Burton et al, 2016;Grabich et al, 2016;Khan et al, 2014;Lane et al, 2013;Rodriguez-Llanes et al, 2016;Schmeltz et al, 2013;Srikuta et al, 2015). Children are more susceptible to injuries, diarrheal diseases, and respiratory infections (Phung et al, 2014).…”
Section: Population Susceptibilitymentioning
confidence: 99%
“…Flooding causes rapid loss of life from physical damage of the disaster but also interrupts food supply and life support, leading to chronic community malnutrition (Su, 2011). Communities that lack health infrastructure or health facilities have poorer health outcomes due to the interruption in transportation that is associated with flooding or other water-related disasters-people cannot get health care during communication or power disruptions (Abbas & Routray, 2014). Food security is related to increased population growth rates, deficiency of drinking water, degradation of soil, urbanization, and animal-based diets, all of which are influenced by climate change (Ahmed et al, 2016).…”
Section: Population Susceptibilitymentioning
confidence: 99%
“…For example, Rahmasary et al [68] found that insufficient solid waste collection and treatment led to sewer clogging and urban flooding in Bandung, Indonesia. Such urban flooding also poses the risk of malaria outbreaks and substantial traffic congestion [69]. Moreover, ground subsidence as a consequence of groundwater over-abstraction aggravates urban flooding.…”
Section: Discussionmentioning
confidence: 99%